2008
DOI: 10.4143/crt.2008.40.2.45
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 Overexpression, p16 Loss, and pRb Inactivation Play a Key Role in Pulmonary Carcinogenesis and have a Prognostic Implication for the Long-term Survival in Non-small Cell Lung Carcinoma Patients

Abstract: The observation that cyclin D1 overexpression, p16 loss and pRb inactivation were largely found in NSCLCs suggests that they play an important role in pulmonary carcinogenesis. Also, their inverse or positive correlations indicate that the G(1)/S cell cycle proteins may act alternatively or synergistically on the mechanisms by which tumor cells escape the G(1) restriction point. Finally, their solitary or combined actions might have a long-term effect on the survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…Loss of p16 protein expression by immunohistochemistry is known to be an accurate method for detection of p16 gene inactivation events [91]. Our observations show that loss of p16 protein expression is frequent in NSCLC (63%) and is an especially common feature of SCC compared to ACA, which is well in line with most previous studies addressing this issue [59,92]. Since most SCC are p16-negative, p16-positive SCC with a nondeleted p16 gene might represent a distinct biological group.…”
Section: Cyclin-dependent Kinase Inhibitorssupporting
confidence: 89%
See 3 more Smart Citations
“…Loss of p16 protein expression by immunohistochemistry is known to be an accurate method for detection of p16 gene inactivation events [91]. Our observations show that loss of p16 protein expression is frequent in NSCLC (63%) and is an especially common feature of SCC compared to ACA, which is well in line with most previous studies addressing this issue [59,92]. Since most SCC are p16-negative, p16-positive SCC with a nondeleted p16 gene might represent a distinct biological group.…”
Section: Cyclin-dependent Kinase Inhibitorssupporting
confidence: 89%
“…In a similar study design, Myong [59 ]also observed that cyclin D1 overexpression, p16 loss and the inactivation of RB (by phosphorylation) are common in NSCLC. Furthermore, cyclin D1 overexpression correlated with p16 loss and RB inactivation and the overall survival of patients with the combination of cyclin D1 overexpression and loss of p16 tended to show a rapid decline [59]. Our own observations of a multitude of cell cycle markers in a comparably large cohort (405 cases) of surgically resected NSCLC revealed that cyclin D1 overexpression is associated with the overexpression of cyclin D3, p27 (nuclear), p21 and the loss of p16 [36,37].…”
Section: Cyclins In Nsclcmentioning
confidence: 91%
See 2 more Smart Citations
“…18,19 Cyclin D1 overexpression and pRB inactivation indicates a poor prognosis. 20 Bcl2 as an anti-apoptotic protein has a more important role in neuroendocrine (NE) lung cancer than in other bronchial-pulmonary carcinomas. 21 Excision repair cross-complementing 1 (ERCC1) genetic polymorphisms may affect patient's response to platinum-based chemotherapy.…”
Section: Introductionmentioning
confidence: 99%